2020
DOI: 10.1186/s41747-019-0142-1
|View full text |Cite
|
Sign up to set email alerts
|

7-T clinical MRI of the shoulder in patients with suspected lesions of the rotator cuff

Abstract: Background: To evaluate feasibility and diagnostic performance of clinical 7-T magnetic resonance imaging (MRI) of the shoulder.Methods: Eight patients with suspected lesions of the rotator cuff underwent 7-T MRI before arthroscopy. Image quality was scored for artifacts, B 1 + inhomogeneities, and assessability of anatomical structures. A structured radiological report was compared to arthroscopy. In four patients, a visual comparison with pre-existing 1.5-T examinations was performed. Results: Regarding imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Compared to 1.5-T MRI, higher contrast and spatial resolution obtained at 7 T led to a better image quality and morphological assessment of alterations of the articular structures, including cartilage. Nevertheless, the diagnostic performance of 7-T MRI did not result superior to the results of 3-T MRI reported in the literature [ 17 ].…”
Section: Cartilagementioning
confidence: 87%
See 4 more Smart Citations
“…Compared to 1.5-T MRI, higher contrast and spatial resolution obtained at 7 T led to a better image quality and morphological assessment of alterations of the articular structures, including cartilage. Nevertheless, the diagnostic performance of 7-T MRI did not result superior to the results of 3-T MRI reported in the literature [ 17 ].…”
Section: Cartilagementioning
confidence: 87%
“…Lazik-Palm et al [ 17 ] first demonstrated the feasibility of shoulder clinical protocol acquisition at 7 T with diagnostic image quality. Compared to 1.5-T MRI, higher contrast and spatial resolution obtained at 7 T led to a better image quality and morphological assessment of alterations of the articular structures, including cartilage.…”
Section: Cartilagementioning
confidence: 99%
See 3 more Smart Citations